Food system transformation and its impact on smallholder farmers' income and food security in Indonesia - Hery Toiba; Tri Wahyu Nugroho; Dwi Retnoningsih; Moh. Shadiqur Rahman (Cogent Economics & Finance, 2020)
Transformation of food system in Indonesia can have a profound impact on the supply chain of smallholder farmers. Policymakers are concerned about the impact of "modern food retail penetration" or "supermarket penetration" on Indonesian food chain participants. This study aims to analyze the link between supermarket penetration and smallholder farmers' welfare. Data were obtained from a survey involving 300 smallholder horticulture farmers from two regencies: Malang and Kediri. The data were analyzed to shed light on these issues. Endogenous switching regression was used to analyze the impact of participation in modern food marketing channel on both food security and welfare. The results of the econometric analysis suggest that there is a link between participation in the modern market and food security. In addition, this study also highlights that the presence of a new system of food supply chain is able to increase smallholder farmers' income through the stability of price and demand.
Keywords: 330; endogenous switching regression; food security; Food system transformation